EXPERIMENTAL STUDY OF THE INFLUENCE OF IRON OXIDE COLLOIDAL SOLUTIONS WITH NANOPARTICLES ON THE CARDIOVASCULAR SYSTEM OF RATS - Trachtenberg, I.M.; Ischeikin, K.Ye.; Dmytrukha, N.M.; Andrusyshyna І.М.; Kozlov, K.P.; Lehkostup, L.A.; Tsapko, V.G. (World of Medicine and Biology, 2022)
The purpose of the study was to establish the toxic effect of Fe2O3 nanoparticles of different sizes on the cardiovascular system after long-term exposure. Experimental rats were injected intraperitoneally 5 times a week with colloidal solutions of Fe2O3 (with particles of 19, 75 and 400 nm) in a dose of 1 mmol (0.112 mg/ml of iron) per 100 g of the rat’s body weight, a total of 30 injections. To establish the cardiotoxic effect of Fe2O3 colloidal solutions, haematological, biochemical and electrocardiographic parameters were determined and compared with the data in the control group. It was established that the long-term intake of Fe2O3 solutions caused disruptions in the process of hemoglobin synthesis; changes in blood coagulation parameters with signs of hypercoagulation; damage to liver and heart cells and increased activity of AST, ALT, AP, LDG, total CK and CK-MB enzymes. The cardiotoxic effect due to the exposure to Fe2O3 colloidal solutions was manifested by disruptions of the contractile and conduction function of the heart. It was noted that the Fe2O3with 19 nm NPs had a more pronounced effect on the cardiovascular system of rats.